RGS10 Deficiency Alleviated Intestinal Mucosal Inflammation Through Suppression of Th1/Th17 Cell Immune Responses in Ulcerative Colitis - Yang, Yonghong; Shao, Yiming; Gao, Xizhuang; Hu, Zongjing; Wang, Yan; Ma, Cuimei; Jin, Guiyuan; Zhu, Fengqin; Dong, Guanjun; Zhou, Guangxi (Immunology, 2025)
ABSTRACT Regulator of G‐protein signalling (RGS) 10 plays critical roles in several immune related diseases. However, whether RGS10 is involved in colonic inflammation of ulcerative colitis (UC) is still obscure. This study aimed to investigate the role of RGS10 in UC. In this study, RGS10 expression was examined by quantitative real‐time polymerase chain reaction (qRT‐PCR), western blotting, immunohistochemistry, and immunofluorescent analysis. Single‐cell RNA sequencing of intestinal mucosa was performed to identify key immune cells with differentially expressed RGS10. RGS10 knockout mice were generated and established dextran sulphate sodium (DSS)‐induced colitis. Expression of inflammatory cytokines on mRNA and protein levels was detected by qRT‐PCR, enzyme‐linked immunosorbent assay, and flow cytometry. We found that RGS10 expression was significantly elevated in UC patients, especially in CD4+ T cells, compared with healthy subjects. Intriguingly, RGS10 deficiency markedly alleviated DSS‐induced colitis and decreased the proportion of Th1 and Th17 cells in lamina propria mononuclear cells (LPMCs), peripheral blood (PB), spleens, and mesenteric lymph nodes (mLNs). Mechanistically, RGS10 deficiency blocked the differentiation of Th1 and Th17 cells by inhibiting the phosphorylation of signal transducer and activator of transcription (STAT) 1 and STAT3. The co‐immunoprecipitation analysis further showed that RGS10 could interact with protein tyrosine phosphatase non‐receptor type 2 (PTPN2), and further regulated Th1 and Th17 cells differentiation of CD4+ T cells. In conclusion, RGS10 deficiency alleviated intestinal mucosal inflammation through inhibition of Th1/Th17 cell‐mediated immune responses via interaction with PTPN2 in CD4+ T cells. Therefore, targeting RGS10 may represent a novel therapeutic approach for UC treatment. RGS10 expression was significantly elevated in inflamed mucosa and CD4+ T cells of UC patients, compared with healthy subjects. Intriguingly, RGS10 deficiency markedly alleviated DSS‐induced colitis and decreased the proportion of Th1 and Th17 cells. Mechanistically, RGS10 deficiency inhibits Th1/Th17 cell‐mediated immune responses via interaction with PTPN2 in CD4+ T cells from UC patients. Therefore, targeting RGS10 may represent a novel therapeutic approach for UC treatment.